2001
DOI: 10.1039/b106118f
|View full text |Cite
|
Sign up to set email alerts
|

Al-MCM-41: its acidity and activity in cyclohexene conversion

Abstract: Investigation of cyclohexene conversion over Al-MCM-41 has shown that the concentrations of Br(nsted and Lewis acid sites increase with the Al content of the materials. The conversion follows mainly two mechanisms: cyclohexene skeletal isomerisation (CSI) and hydrogen transfer (HT). The products with 6 carbon atoms in a molecule prevail in all cases. Some amounts of products with 1 to 8 carbon atoms are also formed as a result of cracking or alkylation. All these reactions can occur at the acidic centres of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It has been reported that the reactivity of cyclohexene on Brønsted acid sites or Lewis acid sites is at variance in reactions such as hydrogen transfer, isomerization, hydration, and alkylation, and higher reactivity of cyclohexene was observed on Brønsted acid sites. Although it can be qualitatively deduced that the lower amount of the Lewis acid sites is beneficial to the higher selectivity to cyclohexene based on the catalytic results of the Ru–B/ZrO 2 -A and Ru–B/ZrO 2 -T catalysts, further work is needed to differentiate the effects of the Brønsted acid sites and the Lewis acid sites on the selectivity to cyclohexene, which may be instructive for the design of Ru catalysts with improved selectivity to cyclohexene in partial hydrogenation of benzene.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the reactivity of cyclohexene on Brønsted acid sites or Lewis acid sites is at variance in reactions such as hydrogen transfer, isomerization, hydration, and alkylation, and higher reactivity of cyclohexene was observed on Brønsted acid sites. Although it can be qualitatively deduced that the lower amount of the Lewis acid sites is beneficial to the higher selectivity to cyclohexene based on the catalytic results of the Ru–B/ZrO 2 -A and Ru–B/ZrO 2 -T catalysts, further work is needed to differentiate the effects of the Brønsted acid sites and the Lewis acid sites on the selectivity to cyclohexene, which may be instructive for the design of Ru catalysts with improved selectivity to cyclohexene in partial hydrogenation of benzene.…”
Section: Resultsmentioning
confidence: 99%
“…The covalent S=O bond is of strong electron induction effect which could shift electron cloud density of Zr−O so that the Lewis acidity is enhanced, and more BrØnsted sites are formed because Zr cation can absorb more water, this is consistent with our Py‐IR characterization results(Figure S1,SI). The Lewis acid and BrØnsted centers directly affect the catalytic activity of SO 4 2− /Zr‐MCM‐41 . It was showed that the cooperation of Zr and SO 4 2− was the main reason that SO 4 2− /Zr‐MCM‐41 was of excellent catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The traditional catalysts for cyclohexene skeletal isomerization are mainly based on metal oxides including silica, alumina, zirconia, titania, or their combinations. It is widely observed that the activity of catalyst is positively correlated to increasing surface acidity 6 , 12 14 . However, highly active catalysts with high surface acidity can promote a series of side reactions such as hydrogen transfer, cracking, and coking, lowering the selectivity towards methylcyclopentene.…”
Section: Introductionmentioning
confidence: 99%